PENGARUH PERSEPSI KUALITAS DAN KEPUASAN PELANGGAN TERHADAP MINAT BELI ULANG PASTA GIGI PEPSODENT ( Studi Kasus Mahasiswa Fakultas Ekonomi Unika Santo Thomas Sumatera Utara) - Manullang, Ida M (Jurnal Manajemen dan Bisnis, 2016)
The purpose of this study to analyze the effect of price and reputation of the company to the perception of quality, and. influence perceptions of quality and customer satisfaction on buying interest again. Benefits Research, provide knowledge to the community, especially for those who want to engage in the business world and is related to the maintenance of the brand as well as maintaining the presence of the customer. For education. Contributing to the academic community about the importance of managing the variables that can affect the buying interest from consumers through the perception of quality and customer satisfaction. Total sample of 96 respondents, the method of collecting data through questioner and documentation, methods of data analysis by regression. The results of the first regression equation: PK = 10.034 + 0,873H + 0,17RP. This means that the variable price and the reputation of the Company has a positive influence on perception of quality. The correlation coefficient (r) = .743. The coefficient of determination (r2) = .552049, meaning that the variable Variable Price and Company Reputation able to explain 55.2% of the Quality Perception, while 44.8% are influenced by other factors. T value (price) is greater than t table means partially Price has a significant effect on the perception of quality. Corporate Reputation While the variable is not significant. F count> F table, then the variable price and the reputation of the Company has a significant influence simultaneously on Quality Perception. The results of the second regression equation: MBU = 6.227 + 0.018 + 0.705 KP PK means that the variable Perception Quality and Customer Satisfaction indicates a positive value towards Interests Buy Re. The correlation coefficient (r) = 0,703 meaning variable correlation Perception Quality and Customer Satisfaction toward Interests Buy Re have a strong relationship. The coefficient of determination of 0.490 or 49.0% variable Perception Quality and Customer Satisfaction able to explain to the Interests Buy Birthday while 51% are influenced by other factors. Tcount variable 0.378 Quality Perception is smaller than ttabel 1960. Then H0 and H1 accepted, meaning variable Quality Perception has no significant effect partially on Interests Buy Birthday while variable customer satisfaction significantly. F count larger than F table, then Ho is rejected and H1 accepted. Perception variable means Quality and Customer Satisfaction has a significant influence simultaneously towards Interests Buy Re. Based on the results of the study should the company need to increase the company's reputation through improved attributes offered through its products. and that companies need to improve the attributes offered by its products so that customers increasingly high quality of perception.